Status of Sustainability Institutional Dimensions in the Development of Mangrove Tracking Area Bungkutoko Island Nambo Sub-District Kendari City - Nastain, Arif; Fyka, Samsul Alam; Limi, Muhammad Aswar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
This study analyzes the sustainability status institutional dimension of mangrove ecosystems in the Bungkutoko mangroves tracking ecotourism area. The study was conducted in September 2019 – March 2020 in the mangrove tracking area of Bungkutoko Island, Nambo District, Kendari City. The method used in this study is a survey method with a purposive sample. The sample in this study amounted to 12 people, consisting of 5 people from the Department of Marine Affairs and Fisheries of Kendari City and seven people who manage the Bungkutoko mangrove tracking. Primary data collection is done through direct observation in the field and structured interviews with the help of questions. Secondary data collection was obtained through literature studies. Analysis of the data used includes quantitative research with the Rapid Appraisal for Fisheries (RAPFISH) method that has been modified to Rap_Mforest and qualitative analysis (descriptive). The result showed the status of sustainability management of mangrove ecosystems. The institutional dimension is in the quite sustainable category (53.67). The attribute leverage analysis on the institutional extent shows that the most sensitive attribute to affect sustainability in the institutional dimension is the role of formal institutions that support mangrove ecosystem management. Even a slight change in this attribute will affect the institutional sustainability of the mangrove ecosystem. The legal institution, in this case, is the Kendari City Government through the Kendari City Marine and Fisheries Service